2010
DOI: 10.4081/ijas.2010.e48
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of pig breeds from Shandong province of China and their influence by modern commercial breeds by analysis of mitochondrial DNA sequences

Abstract: Mitochondrial cytochrome b (Cytb) and partial control region (CR) DNA sequence of 165 individuals were sequenced to determine phylogenetic relationships of eight pig breeds (Laiwu Black, Dapulian Black, Licha Black, Yimeng Black, Yantai Black and Wulian Black, Luyan White and Changwei White) from Shandong province of China, and to what extent they were affected by modern commercial breeds (Landrace, Yorkshire and Duroc) in maternal lineage. The eight breeds from Shandong had lower maternal evolutionary diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our sequencing results are consistent with data from other genetic markers, such as mitochondrial DNA and microsatellite markers (Yang et al, 2003a;Yang et al, 2003b), which have also revealed that European and Chinese indigenous pig breeds are genetically distant. LW and DPL were grouped in a separate cluster in the neighbor-joining trees (Figure 2A) with a close genetic distance of 0.2337, which is consistent with the results of previous mitochondrial DNA sequencing (Wang et al, 2009;Wang et al, 2010). Firstly, the main distribution areas of Laiwu and Dapulian are contiguous.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our sequencing results are consistent with data from other genetic markers, such as mitochondrial DNA and microsatellite markers (Yang et al, 2003a;Yang et al, 2003b), which have also revealed that European and Chinese indigenous pig breeds are genetically distant. LW and DPL were grouped in a separate cluster in the neighbor-joining trees (Figure 2A) with a close genetic distance of 0.2337, which is consistent with the results of previous mitochondrial DNA sequencing (Wang et al, 2009;Wang et al, 2010). Firstly, the main distribution areas of Laiwu and Dapulian are contiguous.…”
Section: Discussionsupporting
confidence: 87%
“…After years of effort, genetic variation and phylogenetic relationships in Chinese indigenous pig breeds have been explored morphologically, cytogenetically, and biochemically (Xiao et al, 2010). With the rapid development of molecular biology technology, research on the nuclear DNA diversity of pigs has increased, including RAPD, microsatellite DNA markers, AFLP, DNA fingerprinting, and mitochondrial DNA sequencing (Ren et al, 2000;Chen et al, 2004;Zhao et al, 2007;Wang et al, 2010). However, the majority of genetic data are still poorly characterized, except in a few very famous breeds.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that that these two breeds are less influenced by Western pig breeds except for some ancestral contribution of Yorkshire into them, and gene flow between them and the other indigenous breeds in Shandong is also rather weak. In our previous study using the control region of mtDNA (Wang et al, 2009 and2010), these two breeds are also grouped into relatively respective sub-clusters in the NJ phylogenetic tree, suggesting there is less gene admixture between them and the other breeds in maternal lineage.…”
Section: Discussionmentioning
confidence: 85%
“…So far, the genetic diversity of some Chinese indigenous pig breeds has been evaluated by microsatellite markers (Fan et al, 2002;Yang et al, 2003b;Zhang et al, 2003;Li et al, 2004;Fang et al, 2005;Megens et al, 2008;Chang et al, 2009) and mitochondrial DNA (mtDNA) sequence (Yang et al, 2003a;Fang and Andersson, 2006;Wu et al, 2007;Wang et al, 2009 and2010). However, the vast genetic resources in China are still poorly characterized except for a few very famous breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the phylogenetic relationships among eight pig breeds from Shandong province of China and to what extent they were affected by the modern commercial breeds (Duroc, Yorkshire and Landrace) were determined in maternal lineage by using direct sequencing of mitochondrial Cytb and partial control region (CR) DNA sequence (Wang et al 2010), two molecular markers widely used to analyze the phylogenetic relationships of closely related groups (Jiang et al 2008). …”
Section: Introductionmentioning
confidence: 99%